Pengelolaan Persediaan Barang Dagangan Bagi Usaha Mikro Di Desa Botubarani, Kecamatan Kabila Bone, Kabupaten Bone Bolango - Muliyani Mahmud; Hartati Tuli (Fakultas Ekonomi Universitas Negeri Gorontalo, 2022)
The goal that they want to achieve from this program is to develop the knowledge of micro-entrepreneurs regarding merchandise inventory management in order to increase their income by minimizing the cost of expired inventory. The method that will be used in increasing the understanding of the micro-enterprise community is training and education for the business community using a lecture and discussion approach conducted by us as lecturers at the UNG Faculty of Economics. In the long term, this program can increase the contribution of the State University of Gorontalo through LPM UNG in the field of community service. Through this service, we try to transfer knowledge to the community of micro business actors in Botubarani Village in managing their inventory. The expected result of this community service is an increase in knowledge and income for the community in Botubarani Village, Kabila Bone District, Bone Bolango Regency, especially micro business actors. Partners in this community service program are the community of micro-entrepreneurs in Botubarani Village.